Gastarbeiters' old age: strategies of life choices among the migrant population of pensioners - Dragana Antonijević (University of Belgrade, 2016)
The focus of our research was on the old age life strategies of retired gastarbeiters. For labor migrants who went to work "temporarily" abroad, becoming pensioners opens up a slew of problematic issues about their social status in host countries. This is a topic which has been neglected in Serbian academia, and has recently attracted the attention of the global scientific community through the attempt to make an interdisciplinary connection between studies of migration and studies of age. So far, the literature on migrant-pensioners has mostly dealt with the topic of "returning" to the home country, however it became evident that a large number of migrants stays in host countries well into old age, hence the recent trend in Europe to consider the issue of their status, pensions and social welfare as well as other forms of support for this, still largely nationally, socially and economically marginalized population. We wanted to examine the situation with Serbian gastarbeiters - are they coming back to their homeland after retiring or not, how they value their old age and what life strategies do they adhere to in retirement.